IMPLEMENTATION OF BEHAVIORISM THEORY-BASED TRAINING LEARNING MODEL IN PHYSICAL EDUCATION IN CLASS VII JUNIOR HIGH SCHOOL FOOTBALL GAME MATERIALS - Mustafa, Pinton Setya (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
This article aims to provide information about learning based on behaviorism learning theory through a drill learning model in football game material in grade VII Junior High School. Behaviorism learning theory, which has the principle of providing a stimulus that results in a response. The stimulus is given by the teacher in the form of material that needs to be done by students, resulting in students responding by doing assignments from the material. Physical education, sports, and health (PESH) learning activities involve moving activities to achieve competence. The game of football is one of the materials used in learning PESH movements. The principle of learning PESH is to involve students to move happily. The drill learning model is an alternative that can be used in soccer learning for seventh-grade students of junior high school. The exercise learning model is repeating movements in sports techniques that have been compiled by the teacher. In conclusion, with a variety of exercise learning models, students can learn PESH material to achieve better and more active sports movements and feel happy. Teachers need to innovate continuously to design learning models that are following the characteristics of students.